Impact of Advanced Age on Survival in Patients Undergoing Resection of Hepatocellular Carcinoma: Report of a Japanese Nationwide Survey. Issue 4 (April 2019) - Kaibori, Masaki; Yoshii, Kengo; Yokota, Isao; Hasegawa, Kiyoshi; Nagashima, Fumio; Kubo, Shoji; Kon, Masanori; Izumi, Namiki; Kadoya, Masumi; Kudo, Masatoshi; Kumada, Takashi; Sakamoto, Michiie; et al.
Abstract : Objective: The impact of age on survival after hepatic resection for hepatocellular carcinoma (HCC) has not been thoroughly examined. We reviewed the data of a nationwide follow-up survey to determine the outcomes of hepatectomy for HCC in elderly patients. Background: Management of malignant diseases in elderly patients has become a global clinical issue because of the increased life expectancy worldwide. Advancements in surgical techniques and perioperative management have reduced age-related contraindications for liver surgery. Methods: In all, 12, 587 patients with HCC who underwent curative hepatic resection were included in this cohort study and classified according to age group [40–59 years (n = 2991), 60–74 years (n = 7576, ), and ≥75 years (n = 2020)]. Clinicopathological features, long-term survival, and cumulative incidences of death after hepatic resection were compared among the groups. The cause-specific subdistribution hazard ratios for 3 types of death depending on age were also estimated. Results: Preoperative liver function tests showed that the prothrombin activity and platelet count were higher in the ≥75-year age group than in the other age groups. The overall survival was significantly lower in the elderly than younger patients. However, recurrence-free survival was almost identical among the 3 groups. The cumulative incidence of HCC-related or liver-related death was almost identical among the 3 groups; however, the cumulative incidence of other causes of death was significantly different. The 60-year subdistribution hazard ratio for other causes of death increased remarkably with increasing age. Conclusions: Elderly patients in this nationwide survey had significantly worse overall survival after hepatectomy than middle-aged and young patients. The cumulative incidence of other causes of death in elderly patients was significantly different from that of HCC-related or liver-related death among the 3 groups. Abstract : Supplemental Digital Content is available in the text